Cystic Hygroma and Monosomy X - Aykut Özek; Mert Turğal; Özgür Özyüncü; Sinan Beksaç (Gynecology Obstetrics & Reproductive Medicine)
Cystic hygroma is a congenital malformation of the lymphatic system. They are associated with chromosomal abnormalities and major structural anomalies. We describe a case of cystic hygroma associated with monosomy X and termination of pregnancy at 14 weeks of gestation.